Discontinuance of criminal proceedings under Art. 62a of the Prevention Drug Abuse Act of 29 July 2005 as a positive measure of the criminal and legal reaction applied against perpetrators who are in possession of soft drugs in a negligible quantity and for personal use - Bartha, Adrian (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
By the Act amendment of 1 April 2011, Art. 62a was incorporated into the original Act, which allows discontinuance of criminal proceedings before issuing an order to initiate an investigation or inquiry against a perpetrator in possession of psychotropic substances or intoxicants, including the case of lesser importance (Art. 62 (1 and 3) of the Act). A necessary condition is to establish that a verdict of a sentence would be pointless because of an offence circumstances and a degree of its social harmfulness. Also a person that is suspected of possession of drugs or psychotropic substances must have them in an insignificant quantity and only for personal use. This paper discusses some legal issues of the above described institution, which introduced a possibility of decriminalization of criminal liability of a perpetrator − a holder of drugs. The author also attempts to assess the effects of adding Art. 62a to the Act by presenting statistical data which illustrate the application of this institution by the prosecution and the criminal court in judicial decisions.